KLASIFIKASI PENYAKIT DAUN SINGKONG MENGGUNAKAN CONVOLUTIONAL NEURAL NETWORK DENGAN ARSITEKTUR RESNET-18 - Micova Juan (JATISI, 2026)
Food crops are plants that produce carbohydrates and proteins, making them a primary source of staple food for the majority of Indonesia's population. Cassava is classified as a food crop because it contains the carbohydrates and proteins needed by the human body. According to data from [1], cassava contributes 28.21% to food consumption in Indonesia. Based on interviews conducted, classifying diseases in cassava leaves is an important step to prevent the spread of infections. However, visual observation-based classification is considered less effective, as it requires expert knowledge, takes a significant amount of time, and is difficult to implement on a large scale. From the results of hyperparameter tuning using the CNN ResNet-18 method, the best model was achieved with 20 epochs, a batch size of 32, and a learning rate of 0.001. This configuration yielded a precision of 94.54%, recall of 94.40%, F1-score of 94.33%, and an accuracy of 94.40%. Additionally, based on the questionnaire results, the average scores for Usefulness were 86.5%, Satisfaction 84.6%, and Ease of Use 88.5%.